Baby schema in human and animal faces induces cuteness perception and gaze allocation in children - Borgi, Marta; Cogliati-Dezza, Irene; Brelsford, Victoria; Meints, Kerstin; Cirulli, Francesca (Frontiers in Psychology, 2014)
The baby schema concept was originally proposed as a set of infantile traits with high appeal for humans, subsequently shown to elicit caretaking behavior and to affect cuteness perception and attentional processes. However, it is unclear whether the response to the baby schema may be extended to the human-animal bond context. Moreover, questions remain as to whether the cute response is constant and persistent or whether it changes with development. In the present study we parametrically manipulated the baby schema in images of humans, dogs and cats. We analyzed responses of 3-6-year-old children, using both explicit (i.e. cuteness ratings) and implicit (i.e. eye gaze patterns) measures. By means of eye-tracking, we assessed children’s preferential attention to images varying only for the degree of baby schema and explored participants’ fixation patterns during a cuteness task. For comparative purposes, cuteness ratings were also obtained in a sample of adults. Overall our results show that the response to an infantile facial configuration emerges early during development. In children, the baby schema affects both cuteness perception and gaze allocation to infantile stimuli and to specific facial features, an effect not simply limited to human faces. In line with previous research, results confirm human positive appraisal towards animals and inform both educational and therapeutic interventions involving pets, helping to minimize risk factors (e.g. dog bites).